Treatment of Obesity with Diethylpropion as an Appetite Suppressant - N Anna Sakinah Liana Rahmawati; Rizky Abdullah; Izzah Faridh (Riviera Publishing, 2026)
Obesity and the Use of Diethylpropion: A Review — Obesity is a medical condition characterized by excessive fat accumulation, elevated body weight, and increased waist circumference. It can manifest at any age and is influenced by various factors, including lifestyle, socioeconomic status, and behavioral patterns. Addressing obesity is critical due to its association with an increased risk of comorbidities. This review aims to evaluate the safety and efficacy of diethylpropion as a short-term pharmacotherapy for obesity. This article is based on a comprehensive literature review conducted across multiple databases, including PubMed, Scopus, Springer, Elsevier, NCBI, and Google Scholar, utilizing the search terms “diethylpropion” and “obesity.” The literature search included studies published between 2015 and 2025. Research indicates that diethylpropion has demonstrated significant reductions in both weight and waist circumference. It is considered safe for patients with a history of hypertension and is associated with minimal side effects. The medication’s effectiveness may be influenced by factors such as the timing of administration, genetic predisposition, and gender. In conclusion, diethylpropion represents a viable option for the short-term management of obesity in patients who have not achieved success through lifestyle modifications.